CYBER CULTURAL COUNSELING AS AN ALTERNATIVE TO PROBLEM SOLVING CULTURE SHOCK OF STUDENTS WHILE DISTANCE LEARNING DURING THE COVID-19 PANDEMIC IN INDONESIA - Susana Aditiya Wangsanata; Sucik Rahayu; Dwi Vianita Rosari (International Conference on Social and Islamic Studies, 2021)
The purpose of this research is to answer the problems of education in Indonesia during the Covid-19 pandemic. Oneform of this problem is the phenomenon of culture shock studentwhen learning distance (online). Thecondition wasculture shock caused by the change in the learning model from what was originally done face-to-face, then carriedout remotely. The form of culture shock is that students feel anxious and nervous when they have to carry outdistance learning. This is none other than due to various obstacles ranging from the availability of learning mediasuch as cellphones, laptops, and internet access (signals). If the condition of culture shock continues to beexperienced by students, it is feared that it will have an impact on students' psychological conditions such asdepression, stress, worry, and other negative mental symptoms. Therefore, it is necessary for the role of the teacherto be able to solve the problem of culture shock . The solution that can be taken by the school is the role of the BK(Counseling Guidance) teacher to provide direction, assistance, and motivation for students to be able to take part inthe distance learning process. The form of assistance and motivation can be in the form of multicultural counselingconducted online or commonly called cyber cultural counseling. Apart from being an alternative form of problemsolving for students who experience culture shock, multicultural cyber counseling is also a form of support for thegovernment to implement social distancing and psychological distancing so that the Covid-19 pandemic can beovercome. This research method is literature by collecting various sources of data that are accurate and relevant tothe focus of this research study. The results of this study indicate that cyber multicultural counseling is amulticultural counseling service that is carried out remotely. The focus of this counseling is to help students to beable to adapt to new situations and conditions, from face-to-face learning culture to distance learning. Then themeasure that multicultural cyber counseling really becomes an alternative problem solvingshock culture is asfollows. First, students need to adapt to the new environment and culture in the learning process, therefore specialattention needs to be paid to understanding the conditions of the learning culture that is currently changing. Thespecial attention is in the form of providing direction, support, and motivation that the Covid-19 pandemiccondition does require adaptation. Second, namely the psychological condition of students who tend to be unstablein accepting new things, such as the Covid-19 pandemic. The unstable psychological condition is caused by thelimited mindset of students regarding the current conditions that actually occur. Therefore, there needs to be properhandling so that the psychological condition of students is able to understand the conditions of the Covid-19pandemic. The handling is by providing educational entertainment that can be provided by the BK teacher. Theform of educative entertainment is adjusted to the creative abilities and competencies of the BK teachers in eachschool. The third is multicultural cyber counseling as a form of support for the government to carry out socialdistancing and psychological distancing so that the Covid-19 pandemic can be completed and can minimize thespread of Covid-19 in school clusters.